2006
DOI: 10.1111/j.1740-8261.2006.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

M‐mode Echocardiographic Parameters and Indices in the Normal German Shepherd Dog

Abstract: M-mode echocardiographic measurements were made from 50 healthy German Shepherd dogs (30 males and 20 females). The dogs were awake and unsedated, in right lateral recumbent position. The following parameters were measured on the echocardiographic images: interventricular septal thickness at end-diastole (IVSd), interventricular septal thickness at end-systole (IVSs), left ventricular internal dimension at end-diastole (LVIDd), left ventricular internal dimension at end-systole (LVIDs), left ventricular poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
8
37
2
1
Order By: Relevance
“…In line with previously published data in growing ponies and Thoroughbred foals [14,28] and in dogs of different breeds [2,3,10], several echocardiographic measurements increased progressively with age in our study, although the groups of age between which significant differences existed varied according to the echocardiographic parameter. The most marked increases in the dimensions of chambers (AOD, ABS, AJT and LV), LVFWT and IVST were found between groups B and C for the fillies and between groups D and E for the colts.…”
Section: Comparison Of the Echocardiographic Measurements In Spanish supporting
confidence: 92%
See 1 more Smart Citation
“…In line with previously published data in growing ponies and Thoroughbred foals [14,28] and in dogs of different breeds [2,3,10], several echocardiographic measurements increased progressively with age in our study, although the groups of age between which significant differences existed varied according to the echocardiographic parameter. The most marked increases in the dimensions of chambers (AOD, ABS, AJT and LV), LVFWT and IVST were found between groups B and C for the fillies and between groups D and E for the colts.…”
Section: Comparison Of the Echocardiographic Measurements In Spanish supporting
confidence: 92%
“…In dogs, several authors reported that gender did not exercise an important effect on echocardiographic parameters [10,29]. By contrast, others presented significant differences linked to the sex in some echocardiographic measurements, although the different BW was not considered [13,18].…”
Section: Comparisons Of Echocardiographic Measurements Between Spanismentioning
confidence: 98%
“…Several echocardiographic parameters correlated positively to body weight in the three breeds included in the present study, in conformity with earlier reports on other populations (Boon et al, 1983;Lombard, 1984;Jacobs and Mahjoob, 1988;Brown et al, 2003;Kayar et al, 2006). Lonsdale et al (1998) demonstrated the effect of training on the IVSs in English Greyhounds, as this value proved to be significantly higher in trained dogs.…”
Section: Discussionsupporting
confidence: 79%
“…In the study of Lonsdale et al (1998), male Greyhounds in training demonstrated higher values of IVSd, LAD and AOD than females. Kayar et al (2006) also reported a significant relationship between gender and LVPW, both in systole and diastole, as well as between gender and FS%. In the study of Vollmar (1999) on healthy Irish Wolfhounds, significant differences were demonstrated regarding several echocardiographic parameters among different body weight and age groups.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have described different M‐mode reference ranges for male and female dogs, for example, in Greyhounds, German Shepherds, and Great Danes 12, 22, 23. In this study, both LVIDd and LVIDs were significantly smaller in female dogs, which had lower body weight than male dogs.…”
Section: Discussionmentioning
confidence: 56%